2014
DOI: 10.3389/fgene.2014.00307
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and pathway analysis of feed efficiency in pigs reveal candidate genes and pathways for residual feed intake

Abstract: Residual feed intake (RFI) is a complex trait that is economically important for livestock production; however, the genetic and biological mechanisms regulating RFI are largely unknown in pigs. Therefore, the study aimed to identify single nucleotide polymorphisms (SNPs), candidate genes and biological pathways involved in regulating RFI using Genome-wide association (GWA) and pathway analyses. A total of 596 Yorkshire boars with phenotypes for two different measures of RFI (RFI1 and 2) and 60k genotypic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 67 publications
5
81
0
1
Order By: Relevance
“…) and might associated with residual feed intake in pigs (Do et al . ). Cell division cycle associated 7 ( CDCA7 ), a candidate gene of several diseases determined by previous studies, may be linked to blood pressure (He et al .…”
Section: Discussionmentioning
confidence: 97%
“…) and might associated with residual feed intake in pigs (Do et al . ). Cell division cycle associated 7 ( CDCA7 ), a candidate gene of several diseases determined by previous studies, may be linked to blood pressure (He et al .…”
Section: Discussionmentioning
confidence: 97%
“…Hence, the RFI may be a relevant trait to consider in selecting genetically superior animals for breeding studies. Genome-wide association studies (GWAS) characterizing the gene expression and gene regulatory mechanisms related to feed efficiency are quite established in pigs (and poultry) [20, 21]; however, such studies in dairy cattle are fairly recent [22]. In this study, we used an RFI adjusted for stage of lactation, management group, breed and parity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the MC4R gene is an important determinant of FE12131415. Moreover, XIRP2, TTC29, SOGA1, MAS1, GRK5, PROX1, GPR155, and ZFVE26 have also been recognized as candidate genes for RFI in pigs16.…”
mentioning
confidence: 99%